Neurotic Solution Of Alif On Finding His Bright Future Of Education In Ahmad Fuadi's The Land Of Five Towers (2011) Novel: An Interpersonal Psychoanalityc Approach - Rahayu, Tiyas Puji, Dr. Phil. Dewi Candraningrum, M.Ed, Siti Fatimah, S. Pd, M. Hum (2014)
The major issue of this study is How is Neurotic Solution of Alif on Finding His Bright Future of Education in The Land of Five Towers by Ahmad Fuadi (2011) related to interpersonal psychoanalytic?. The objective of this study is to analyze The Land of Five Towers Novel written by Ahmad Fuadi based on the structural element of the novel and to describe effort finding His Bright Future of Education in The Land of Five Towers by Ahmad Fuadi related to interpersonal psychoanalytic. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The primary data source is the novel of Ahmad Fuadi published by Gramedia Pustaka Utama (GPU). The secondary data sources are books or any information related to the practice of effort being a journalist that supported the interpersonal psychoanalytic analysis. The data collection method is library research by collecting both primary and secondary data. The data analysis method is descriptive qualitative analysis based on psychoanalytic approach. The results of the study show; firstly, based on the structural element there are messages from the character within the novel consists of two kinds of characters, major and minor character. Setting of place of The Land of Five Towers novel located in Ponorogo, Bukittinggi, and America. The plot of the novel is where the story tells about Alif's live after graduating from Madani Pesantren. The theme of the novel needs not to be moral or message; it may be what the story is about. Dealing with the problem in the research analysis, the theme of this novel is "The human strong passion and pray are the major spirit to reach the dream". The neurotic anxiety appears where there is moving toward people it is when ALif feels that he feels disappointed to his friend Randai. Alif tries to show his responsibility to his friend and he wants to show his sorry with him. The moving against people tells a situation where his mother "Amak" asks Alif to go to Islamic school. But, Alif really wants to go to public school because he has not gifted with religious knowledge. The moving away people appears when he faces the problem related with his future school. Alif finds out that he can not go to the public school. This becomes his problem that fills his head and heart